Pengaruh CEO Duality Terhadap Financial Performance Dengan Earnings Management Sebagai Variabel Intervening - Livia Lemmuela Putri; Devie Deviesa (Business Accounting Review, 2017)
Research on the affect of CEO Duality to Financial Performance had been widely studied previously, but the results were not consistent. Moreover, there were differences in theoretical view on CEO duality based on Stewardship Theory and Agency Theory.  The purpose of this research was to test the direct affect of CEO duality on financial performance by using earnings management as the intervening variables.The data obtained for this research were secondary data by using annual report and financial report. The Sample of this research was companies listed in Indonesian Stock Exchange and the hypothesis in this research was tested by using Partial Least Square (PLS) with the SmartPLS 2.0 program. The result of this research revealed that, CEO duality significantly affected financial performance directly, and indirectly influenced through the intervening variable which was earnings management.